Prognostic performance of combined use of high-sensitivity troponin T and creatine kinase MB isoenzyme in high cardiovascular risk patients with end-stage renal disease - Khaled Abdul-Aziz Ahmed; Wahda Mohammed Al-Attab (The Korean Society of Nephrology, 2017)
Background: The principal goal of this study was to determine the importance of high-sensitivity troponin T (hs-TnT) and creatine kinase MB isoenzyme (CK-MB) in predicting cardiovascular events in asymptomatic end-stage renal disease (ESRD) patients. Methods: This study included 110 participants; 54 ESRD patients undergoing hemodialysis and 56 healthy control participants. Biochemical parameters and cardiac markers were estimated. Comparative utilities were assessed through logistic regression and receiver operating characteristic (ROC) analyses. Results: We found that 96.3% of ESRD patients had an elevated level of hs-TnT (mean, 0.049 ± 0.0324 μg/L) compared to healthy participants. Among patients with ESRD, hs-TnT showed significant correlations with the low-density lipoprotein cholesterol/high-density lipoprotein cholesterol (HDL-C) (P = 0.042, r = 0.278) and total cholesterol/HDL-C (P = 0.044, r = 0.276) ratios. CK-MB (odds ratio [OR], 1.138; P = 0.04) and hs-TnT (OR, 2.153; P = 0.017) predicted cardiovascular events on logistic regression analysis, and the prediction was improved by the model that combined two cardiac markers. The diagnostic performance of hs-TnT and CK-MB alone and the combination of the two biomarkers was assessed by the area under the ROC curve (AUC). The highest AUC was produced by the combination of hs-TnT and CK-MB markers (0.920) compared to hs-TnT or CK-MB alone. Conclusion: In asymptomatic patients with ESRD, hs-TnT appeared to be an important predictor for cardiovascular mortality, and its diagnostic accuracy improved with CK-MB. This study provides new insights into the predictive value of multiple biomarkers for identifying cardiovascular events in ESRD patients on hemodialysis.